JURNALISME DAN WAWANCARA KURSI KOSONG MENTERI TERAWAN (ANALISIS SEMIOTIKA ROLAND BARTHES DALAM EPISODE WAWANCARA KURSI KOSONG MATA NAJWA TAHUN 2020) - Ressa Seftiana; Abdul Fadli Kalaloi (Medium: Jurnal Ilmiah Fakultas Ilmu Komunikasi, 2022)
Journalism on television is present as a bridge for society in fulfilling everyone's right to obtain information that is in accordance with the facts. Senior journalist Najwa Shihab came with a different spectacle that had never happened in Indonesia, he presented an interview with an empty chair. This study uses a constructivist paradigm with descriptive qualitative research methods through the semiotic approach of Roland Barthes. The purpose of this study is to describe how the vacant seat interview show "Mata Najwa" can represent an empty seat as Minister of Health of the Republic of Indonesia Terawan Agus Putranto. This research shows that the show “Mata Najwa” titled #MataNajwaMenantiTerawan represents an empty seat as Minister Terawan with an analysis of denotation, connotation, and myth. The results of this analysis were obtained through taking pictures, the sentences spoken and the meaning of myths in the "Mata Najwa" impressions of the empty chair interview.